Does Time Budget Pressure Moderate the Determinant Factor of Audit Quality? - Meisyarah, Wijdania; Mappanyukki, Ratna (PT FORMOSA CENDEKIA GLOBAL, 2024)
The objective of this study is to empirically analyze the impact of work-life balance, turnover intention, and workload on audit quality. Additionally, the study aims to examine the moderating effect of time budget pressure on the relationship between work-life balance, turnover intention, workload, and audit quality. The research population comprised 81 active Public Accounting Firms based in South Jakarta. The sample consisted of 159 auditors selected through simple random sampling. Statistical analysis was conducted using Smart PLS version 4.1.0.0. The findings of the study are as follows: (1) Work-life balance positively impacts audit quality. (2) Turnover intention negatively impacts audit quality. (3) Workload positively impacts audit quality. (4) Time budget pressure does not moderate the relationship between work-life balance and audit quality. (5) Time budget pressure does not moderate the relationship between turnover intention and audit quality. (6) Time budget pressure does not moderate the relationship between workload and audit quality. This research suggests that future studies could explore other moderating variables besides time budget pressure. Additionally, auditors and Public Accounting Firms can utilize these findings to implement work-life balance strategies, manage turnover rates, and enhance skills to manage workload effectively.